Translational And Cultural Barriers In Understanding Tourism Expressions In English And Uzbek - M.Kurbanova (European International Journal of Pedagogics, 2026)
Tourism expressions function as essential linguistic tools for promoting destinations and shaping travelers’ perceptions. Nevertheless, translating these expressions between English and Uzbek presents significant challenges due to cultural, semantic, and pragmatic differences. This study examines the primary translational and cultural barriers encountered in interpreting tourism discourse, with a particular focus on metaphorical shifts, socio-cultural references, and pragmatic adaptation strategies. The research highlights that effective intercultural communication in tourism requires a balanced translation approach that preserves the original emotional tone while ensuring cultural relevance and resonance. Findings suggest that careful attention to cultural norms, metaphorical conventions, and politeness strategies enhances both the accuracy and persuasive power of translated tourism materials.